Research on the Cultural Characteristics of Glove Puppetry Costumes in Southern Fujian - Kong, Yufei; Chaiyakut, Pongdej; Panthupakorn, Poradee (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The Minnan Glove Puppetry, a pivotal element of traditional Chinese opera, boasts a rich costume culture that encapsulates the distinct folk characteristics and aesthetic sensibilities of the Minnan region in Fujian. Despite its cultural richness, the limited regional reach and outdated dissemination methods have significantly hampered its wider recognition and influence. This study is dedicated to a comprehensive exploration of the underexplored aspects of Minnan Glove Puppetry’s costume culture, particularly its intricate artistic expressions and profound cultural values within traditional drama contexts. It seeks to propose effective strategies for the protection and inheritance of this invaluable intangible cultural heritage, aiming to bolster its popularity and relevance both locally and globally. Materials and Methods: Employing a blend of comprehensive literature review and meticulous field investigations, this research delves deeply into the unique costume culture of Minnan Glove Puppetry. The team conducted field visits to the Jinjiang Puppet Art Protection and Inheritance Center in Quanzhou, where they employed specialized techniques in data collection, including observational studies and structured interviews, to gather primary data on costume design, production processes, and usage in performances. Concurrently, the study features targeted case analyses of costumes from three emblematic plays: "Da Ming Fu", "Nu Zhong Kui", and "Li Dong Jia Xun An", aiming to highlight their role in cultural narration and their artistic significance. Results: The investigation reveals that Minnan Glove Puppetry costumes transcend mere aesthetic roles, serving as vital conduits for the rich cultural essence of the Minnan region. The intricate patterns, vibrant colors, and distinctive shapes of these costumes do not merely adorn; they communicate deep-rooted historical narratives and cultural values, acting as non-verbal lexicons of Minnan’s heritage. Recognizing these costumes as dynamic cultural narrative tools, the study underscores their potential in offering modern audiences novel insights and a richer, more engaging cultural experience. Conclusion: To safeguard and perpetuate the costume culture of Minnan Glove Puppetry, it is imperative to adopt a more action-oriented and forward-looking approach. This includes the integration of costume culture into interdisciplinary research frameworks that meld art, anthropology, and technology, thus enriching the academic and practical understanding of these traditional costumes. Additionally, embedding Glove Puppetry into educational curricula will not only enlighten but also ignite the passion of younger generations for this traditional art. Leveraging digital technologies to preserve and showcase these costumes, coupled with encouraging designers to blend traditional elements into contemporary designs, will significantly enhance their market appeal and cultural resonance. Furthermore, fostering community engagement, international collaborations, and leveraging cultural assets for economic development are critical for amplifying the global presence and impact of Minnan Glove Puppetry.